Treatment of Proclined Upper Incisors with Reverse Bracket Placement: A Case Report - Vu, Chau Tran Bao (2026)
Accurate bracket placement plays a key role in orthodontic treatment outcomes. This case report describes the management of a 21-year-old female presenting with labially inclined maxillary incisors and a midline diastema. Fixed appliance therapy was carried out with a specific adjustment; the brackets on the upper incisors were placed in reverse orientation to improve labial root torque and control the incisor inclination while avoiding additional auxiliaries or tooth extraction. After 25 months of treatment, the patient showed well-aligned teeth, a functional overjet and overbite, closure of the diastema, and a more pleasing smile. Radiographic evaluation suggested that root resorption was minimal. Reverse bracket placement may be a useful alternative in selected cases. Monitoring over time is still necessary to confirm long-term stability.